A review of Salmonella enterica with particular focus on the pathogenicity and virulence factors, host specificity and antimicrobial resistance including multidrug resistance - Jajere, Saleh Mohammed (Veterinary World, 2019)
Salmonella genus represents the most common foodborne pathogens frequently isolated from food-producing animals that is responsible for zoonotic infections in humans and animal species including birds. Thus, Salmonella infections represent a major concern to public health, animals, and food industry worldwide. Salmonella enterica represents the most pathogenic specie and includes >2600 serovars characterized thus far. Salmonella can be transmitted to humans along the farm-to-fork continuum, commonly through contaminated foods of animal origin, namely poultry and poultry-related products (eggs), pork, fish etc. Some Salmonella serovars are restricted to one specific host commonly referred to as "host-restricted" whereas others have broad host spectrum known as "host-adapted" serovars. For Salmonella to colonize its hosts through invading, attaching, and bypassing the host's intestinal defense mechanisms such as the gastric acid, many virulence markers and determinants have been demonstrated to play crucial role in its pathogenesis; and these factors included flagella, capsule, plasmids, adhesion systems, and type 3 secretion systems encoded on the Salmonella pathogenicity island (SPI)-1 and SPI- 2, and other SPIs. The epidemiologically important non-typhoidal Salmonella (NTS) serovars linked with a high burden of foodborne Salmonella outbreaks in humans worldwide included Typhimurium, Enteritidis, Heidelberg, and Newport. The increased number of NTS cases reported through surveillance in recent years from the United States, Europe and low- and middle-income countries of the world suggested that the control programs targeted at reducing the contamination of food animals along the food chain have largely not been successful. Furthermore, the emergence of several clones of Salmonella resistant to multiple antimicrobials worldwide underscores a significant food safety hazard. In this review, we discussed on the historical background, nomenclature and taxonomy, morphological features, physical and biochemical characteristics of NTS with a particular focus on the pathogenicity and virulence factors, host specificity, transmission, and antimicrobial resistance including multidrug resistance and its surveillance.